1959
DOI: 10.1002/qj.49708536410
|View full text |Cite
|
Sign up to set email alerts
|

The composition of precipitation at Lerwick, Shetland

Abstract: SUMMARYIt is shown that most of the salts deposited at Lerwick arrive as sea-spray rather than in true precipitation. Mg, K and Na are present in very nearly the same proportions as in sea water : but there is a very great deficiency of chlorine, which, it is argued, can only be explained on Cauer's hypothesis that NaCl in aerosol form is dissociated and that C1 or HCl is released.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1960
1960
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Cauer (1949, p. 229;, p. 1131 has suggested that sea-salt particles may be oxidized by atmospheric ozone, releasing free chlorine gas which is eventually transformed to hydrochloric acid, and substituting bicarbonate for chloride in combination with the sodium ions. This process is not likely to be quantitatively important (Eriksson, 1960, p. 77), although it has been argued recently by Oddie (1959). A greater likelihood of decomposition would appear to arise from the mixing of sea-salt particles with sulfuric-acid droplets from 1958, p. 500) likewise appears to contain rather pure sea water, except for the addition of considerable calcium and bicarbonate from calcareous sand dunes (Hutton, 1958, p. 289).…”
Section: Sources Of Atmospheric Supp£vmentioning
confidence: 98%
“…Cauer (1949, p. 229;, p. 1131 has suggested that sea-salt particles may be oxidized by atmospheric ozone, releasing free chlorine gas which is eventually transformed to hydrochloric acid, and substituting bicarbonate for chloride in combination with the sodium ions. This process is not likely to be quantitatively important (Eriksson, 1960, p. 77), although it has been argued recently by Oddie (1959). A greater likelihood of decomposition would appear to arise from the mixing of sea-salt particles with sulfuric-acid droplets from 1958, p. 500) likewise appears to contain rather pure sea water, except for the addition of considerable calcium and bicarbonate from calcareous sand dunes (Hutton, 1958, p. 289).…”
Section: Sources Of Atmospheric Supp£vmentioning
confidence: 98%
“…The modification of sea-salt particles has been of interest in connection with the origin of atmospheric gaseous chlorine in the field of air chemistry (e.g., Oddie, 1959;Junge, 1956Junge, , 1963Martens et al, 1973;van de Vate et al, 1978;Okada et al, 1978Okada et al, , 1989. Junge (1963) reviewed that the Cl/Na ratios in rainwater were always smaller than that in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Junge (1963) reviewed that the Cl/Na ratios in rainwater were always smaller than that in seawater. For example, Oddie (1959) found monthly averages of Cl/Na ratios in rainwater were 1.17 to 1.69 in Lerwick on the Shetland Islands. Junge (1963) explained that these results were due to the modification of NaCI reacting with H2SO4 and/or HNO3.…”
Section: Introductionmentioning
confidence: 99%